Language and intergroup perceptions amongst ethnic groups : A case of "Kadazandusun" in Kudat, Sabah - Jeannet Stephen (Universiti Malaysia Sabah, 2004)
This paper will present a case stUdy of ethnic language and intergroup perception done in the Kudat district of Sabah in Malaysia. In this particular case study, the researchers focused on the Rungus ethnic, community's perception on the ethnic language 'Kadazandusun' which has institutional support from the government. The Kadazandusun is the largest ethnic community in multi ethnic Sabah and the community has recently undergone an encouraging and positive language revitalisation process with various milestones to its credit - one of which is the setting up of the successful Kadazandusun Language Foundation. Both ethnic communities are amongst more than 30 indigenous ethnic communities in the State. The idea generally promoted by the KadazandusUll 1 political elders is that the Rungus and other non-Muslim indigenous ethnic communities in the State are also Kadazandusun. Nevertheless, there are cer1ain quarters which say that it is only so culturally, and not linguistically. Thus, following the successful revitalisation of the Kadazandusun ethnic language, other ethnic communities would like to follow suit. However, the only recognised ethnic language as a school subject, at present, is the Kadazandusun language. This research explains the complex multilingual/multiethnic context 'in Sabah from the perspectives of the researchers who live in and observe such context daily. Most importantly, as was analysed from content analysis of , this paper discusses the perception of the Rungus community on issues such as ethnic language revitalisation; processes of language legitimisation in a multiethnic and multilingual region; and on the defmition of ethnic identity in multiethnic Sabah. In a country which is multilingual, multiethnic and multiracial as Malaysia generally, and Sabah specifically, the issues discussed in this paper bear direct and pertinent relevance to the larger theme of the survival of the ethnic groups in Sabah in terms of ethnicity and language.